Formulasi Sediaan Pasta Gigi Gel Minyak Atsiri Daun Jeruk Nipis (Citrus Aurantifolia) Dengan Variasi Konsentrasi Carbomer 940 Sebagai Basis Gelling Agent - Nurista Dida Ayuningtyas; Agustina Putri Pitarisa Sudarsono; Anastasiya Sisca Yuswanti (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Background : Lime leaves contain flavonoids, tannins, and saponins. This content is known to have activity as an antibacterial and protective of gums and teeth. Based on these activities, lime leaves can be developed as an active ingredient in gel toothpaste preparations. In the manufacture of gel toothpaste, the component that plays an important role is the gelling agent. Purpose: In this study, a variation of the gelling agent Carbomer 940 will be used to make a gel toothpaste with lime leaf extract. Methods: The independent variable used is Carbomer 940 with a variation of 3 formulas, namely 0.6%; 1.2%; and 1.8%. The evaluations carried out on gel toothpaste were organoleptic, homogeneity, pH, adhesion, spreadability and pH. Data analysis was carried out with SPSS software to see the differences between each formula. Results: The results showed that the formula 1-3 was homogeneous with a clear, homogeneous color, and a characteristic smell of menthol with a pH range of 5.85-7.49; spreading area 20.60-29.91 cm2, adhesion 6.01-35.1 seconds. The results of statistical tests with one-way ANOVA obtained a significant difference between each formula.